(untitled) (Research, Society and Development, 2021)
Objective: Analyze and reflect on the creation of a mobile application for Oncology Nursing from a professional perspective. Methodology: This research has a qualitative and quantitative approach based on the content analysis methodology by Bardin, it was carried out with 17 specialist nurses in Oncology Nursing working at a cancer patient care institution. Due to the COVID-19 pandemic, was carried out at first in character virtual and after in-person vaccination. Data were collected from transcripts of virtual and face-to-face meetings and analyzed from Bardin’s perspective. Results: In the analysis, it was possible to observe that professionals identify digital technology as a means of training in the workplace and the development of a tool aimed at Oncology Nursing would add reliable and useful knowledge. Final considerations: The object of study found support in the considerations of all the groups presented. It was observed that, regardless of the chosen functional structure, it is of great importance for the Nursing category to have quick access to permanent health education focused on cancer.